Relação da influência antropogênica e da complexidade de habitat sobre a diversidade funcional da ictiofauna em um reservatório Neotropical. - Nascimento, Carolina Pedrozo do (2021)
Reservoirs shores are usually colonized by submerged macrophytes, which have a high influence over the functional diversity of fish assemblages. However, there are also intense anthropogenic activities in these habitats, which may affect the functional structure of fish communities as well. Thus, aiming to evaluate the influence of anthropogenic activities and habitat complexity, provided by submerged macrophytes, on the functional diversity of the ichthyofauna of reservoirs, sampling was carried out in three sites in the marginal areas of the Itaipu reservoir, in places near and apart artificial beaches, with and without submerged macrophytes. Functional traits used were morphometric measurements taken from the sampled individuals (intraspecific traits), which were used to calculate three functional diversity indexes: functional richness, evenness and divergence. In general, we found no patterns in functional diversity indexes regarding the distance from artificial beaches (among sampling stations). In contrast, habitat complexity influenced the functional diversity of fish assemblages, which presented different results depending on macrophytes density. While functional richness increased in higher complexities, the opposite occurred considering functional evenness. Additionally, functional divergence was higher in regions without macrophytes. In conclusion, this study improves the knowledge on the importance of different habitats in the maintenance of the functional diversity of fishes in habitats of reservoirs shores, supporting the implementation of management and conservation strategies in these environments.